Low Serum Acylated Ghrelin Levels are Associated with the Development of Cardiovascular Disease in Hemodialysis Patients - Chou, Chia-Chi; Bai, Chyi-Huey; Tsai, Shiow-Chwen; Wu, Mai-Szu (Internal Medicine, 2010)
Background Ghrelin has a protective effect on endothelial cells. Endothelial cell dysfunction is associated with cardiovascular disease (CVD) and CVD remains the leading cause of morbidity in hemodialysis (HD) patients. Acylated ghrelin (A-Ghr) is the functional form of ghrelin, so we hypothesized that A-Ghr is associated with the occurrence of CVD in HD patients. Methods We conducted a prospective cohort study in 412 HD patients. The cohort was sub-grouped into low and high A-Ghr groups according to the median A-Ghr level of 4.88 pg/mL. The association between the low/high A-Ghr groups and the incidence of CVD were analyzed. Results The HD patients in a low A-Ghr group had a greater risk of incidental CVD than those in a high A-Ghr ghrelin. This association remained significant after the adjustment for possible confounding factors, including age, gender, HD duration, BMI, diabetes, albumin, nPCR and Charlson's comorbidity index score. Conclusion It appears that a low serum A-Ghr level is associated with the development of CVD in HD patients.